MOTIVATING CONSUMERS TOWARDS A COMMON GOAL: A PERSUASION STRATEGY RELYING ON FACTSOR EMOTIONS - Fitriana; Agusiady, Ricky; Aripin, Zaenal (Organisasi Kreatif Indonesia Emas, 2024)
In an increasingly complex and diverse marketing world, the use of persuasion strategies that combine facts and emotions is becoming increasingly important to motivate consumers toward a common goal with a particular brand or product. This research aims to explore the most effective strategies for integrating facts and emotions in marketing, as well as to analyze how contextual factors such as product type, consumer demographics and media platforms influence their implementation. By collecting data from various literature sources, this research presents an in-depth understanding of the concept of persuasion strategies that combine facts and emotions, as well as identifying contextual factors that influence its implementation. The research results show that a holistic approach that integrates a strong story or narrative with relevant facts is the most effective strategy in combining facts and emotions. However, contextual factors such as product type, consumer demographics, and media platforms play an important role in determining the most appropriate strategy. This research provides valuable insights for marketing practitioners to develop persuasion strategies that are more relevant and effective in motivating consumers towards shared goals with a particular brand or product.